1990
DOI: 10.1007/bf01313157
|View full text |Cite
|
Sign up to set email alerts
|

Resuspension and growth ofOstrea edulis: A field experiment

Abstract: Field experiments with Ostrea edulis L. were conducted to examine the effects of resuspension on subtidal oyster growth in a small cove in malifax County, Nova Scotia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…Because scallops are mobile active suspension feeders, their epibionts experience changes in environmental conditions. Increased water flow produced by scallop movements and respiratory activity leads to the resuspension of bottom sediments and, thereby, improves the oxygen conditions and food supply of endobionts, including spionid polychaetes (Grant et al 1990, Hentschel 2004). Wisshak & Neumann (2006) also found that the boring Polydora complex similarly takes advantage of organic matter resuspended by echinoid Echinocorys ovata locomotion and feeding activity.…”
Section: Topical Relationshipsmentioning
confidence: 99%
“…Because scallops are mobile active suspension feeders, their epibionts experience changes in environmental conditions. Increased water flow produced by scallop movements and respiratory activity leads to the resuspension of bottom sediments and, thereby, improves the oxygen conditions and food supply of endobionts, including spionid polychaetes (Grant et al 1990, Hentschel 2004). Wisshak & Neumann (2006) also found that the boring Polydora complex similarly takes advantage of organic matter resuspended by echinoid Echinocorys ovata locomotion and feeding activity.…”
Section: Topical Relationshipsmentioning
confidence: 99%
“…The presence of suspended clay (20 mg/L) interferes with the ability of juvenile eastern oysters to preferentially ingest algae, but does not reduce the overall amount of algae ingested (Urban and Kirchman 1992). The summer growth of European oysters (Ostrea edulis) in the field was enhanced at low levels of sediment resuspension and inhibited as sediment deposition increased (Grant, Enright, and Griswold 1990). Sediment chlorophyll in suspension at low levels may act as a food supplement, thus enhancing growth, but at higher concentrations may dilute planktonic food resources and suppress food ingestion.…”
Section: Juvenile and Adult Stagesmentioning
confidence: 99%
“…The threshold is determined by sediment grain size, sediment density and the influence of biota on sediment strength. In a laboratory experiment, Grant et al (1990) demonstrated that low concentrations of suspended sediment, when swirled up 0.1 cm/day, can contribute to nutrient intake and, as such, have a positive effect on the growth speed of Ostrea edulis, but that sediment churned up to 0.8 cm per day reduces growth. Tolerance of sea bed motion of up to 0.8 cm/day is therefore assumed.…”
Section: Sea Bed Motionmentioning
confidence: 99%